European cities in the face of sustainable development - Derlukiewicz, Niki; Mempel-Śnieżyk, Anna (Ekonomia i Prawo. Economics and Law, 2018)
Motivation: The paper rises the issue of sustainable development in the context of challenges that present cities face. Development of innovative and sustainable economy is an aim for the whole society in the European Union. Three pillars of sustainable development: economic growth, environmental management and social inclusion are fundamental and occur across all economic sectors. Predominantly, they influence cities e.g. fast urbanization process, infrastructure, energy development as well as transportation. Cities in Europe are precursors of the transformation towards a low carbon and resource efficient economy. City authorities are planning and acting towards a more sustainable future characterized by investing in innovative, integrated technologies and services such as buildings, mobility, lighting and broadband communications. Aim: The aim of the article is to present challenges facing European cities in the light of sustainable development. The paper explores trends in regional policy undertaken by the European Union relating to sustainable development. The first part outlines the global vision of present and future goals of sustainable development in the world. The next part focuses on the cities and challenges they face referring to sustainable and smart development. Results: The conducted research shows sustainable development as still valid, important and topical. The research indicates that the structures of the EU are not the exclusively supportive and responsible for sustainable development in Europe. The entities such as cities play a very important role in achieving sustainability. Numerous European cities are still establishing programs integrating the energy, transport and ICT sectors in order to deliver more efficient services to their inhabitants. Finally, more and more cities are going to become smart in the nearest future.